Clinical significance of preoperative nutrition and inflammation assessment tools in gastrointestinal cancer patients undergoing surgery: a retrospective cohort study - Valentina Casalone; Sara Erika Bellomo; Enrico Berrino; Enrico Berrino; Simona Bo; Enrica Favaro; Alfredo Mellano; Elisabetta Fenocchio; Caterina Marchiò; Caterina Marchiò; Anna Sapino; Anna Sapino (Frontiers in Nutrition)
BackgroundMalnutrition and inflammation are associated with poorer surgical outcomes in patients with gastrointestinal cancer. However, it is still debated which parameters should be used to assess nutritional and inflammatory status. The aim of the present study was to investigate the prognostic role of specific parameters in predicting postoperative outcomes in this specific subgroup of patients.MethodsThis retrospective study included 391 adult patients. Malnutrition risk, was assessed by preoperative validated Malnutrition Universal Screening Tool (MUST) score ≥2, lymphocyte count <900 n/mm3, albumin value <3.5 g/dL or a combination of the previous two parameters, the Prognostic Nutritional Index (PNI) < 45; inflammation was evaluated using preoperative Neutrophil-to-Lymphocyte Ratio (NLR) > 5, Platelet-to-Lymphocyte Ratio (PLR) > 150 and Lymphocyte-to-Monocyte Ratio (LMR) < 5. Statistical analysis was carried out using Univariate and Multivariate Analysis and General Linear Models.ResultsPatients with higher preoperative MUST score (p < 0.0001), lower albumin level (p = 0.0002) or lower PNI (p = 0.002) had a greater need for parenteral nutrition support and a longer hospital stay was reported in patients with higher MUST score (p < 0.0001), lower albumin (p < 0.0001), lower PNI (p = 0.0002), higher NLR (p = 0.005) or lower LMR (p = 0.027). Complications were more common in patients with a higher MUST score (p = 0.029), lower albumin (p = 0.008) or lower PNI (p = 0.006). A MUST score ≥ 1 or a PNI < 45 was associated with a two-fold risk of postoperative complications (p = 0.008; p = 0.001), whereas albumin levels <35 g/L were correlated with a Three-fold risk of postsurgical complications (p = 0.008). OS was also worse in patients with higher MUST score (p = 0.004), PNI (p = 0.031) or NLR (p = 0.0002), with a three-fold risk of not surviving at 1 year in patients with a MUST score ≥2 (p = 0.003) or NLR ≥ 5 (p = 0.0003). Using general linear models for repeated measures, a preoperative MUST score >1 or albumin levels < 35 mg/dL was associated with lower postoperative erythrocyte cells and hemoglobin levels. Multivariate analysis confirmed MUST score, PNI and NLR as independent prognostic factors for survival or postoperative complications.ConclusionThe presence of preoperative malnutrition and/or inflammation is associated with worse postoperative outcomes in patients with gastrointestinal cancer. Early nutritional assessment, including all the above parameters, may allow more tailored intervention to reduce the risk of adverse postoperative outcomes.